Computed tomography of Lipiodol‐loaded biodegradable pasty polymer for implant visualization. (6th March 2014) - Sosna, Jacob; Havivi, Ehud; Khan, Wahid; Appelbaum, Liat; Nyska, Abraham; Domb, Abraham J.
<x xml:space="preserve">Abstract</x> Targeted delivery of drug‐loaded implants for regional drug therapy has become an important approach to therapy. Simple and reproducible imaging methodologies to evaluate the implant noninvasively are needed. The goal of this work was to noninvasively evaluate the visibility, shape and degradation of a biodegradable implant containing Lipiodol (an X‐ray contrast medium) by computed tomography (CT). For in vitro evaluation, Lipiodol was incorporated in poly(sebacic‐co‐ricinoleic acid) [P(SA:RA)], a biodegradable injectable pasty polymer, and CT visibility was assessed. For ex vivo evaluation, bovine liver was injected with the polymer‐loaded Lipiodol; for in vivo evaluation rats were injected subcutaneously with Lipiodol in polymer and CT was performed. We show that polymer diameter at CT correlates with implant weight and pathological measurements. Polymer formulation containing 5% Lipiodol was visible on CT in vitro. Ex vivo tests showed a round polymer deposit at the injection site compared with free dispersion of Lipiodol alone. Correlation between implant size at CT scan and surgery at 48 h was R2 = 0.78. Average CT diameter at 9 days was 14.2 ± 2.8 mm in rats injected with Lipiodol in the polymer formulation, as compared with 7.3 ± 1.1 mm in controls. After 9 days, the implant degraded into several zones containing inflammatory cells seen on CT as areas with increased heterogeneity. In conclusion, Lipiodol incorporated in P(SA:RA) is visible on CT, and polymer degradation can potentially be monitored noninvasively. This method can be widely applied to follow changes in biodegradable implants. Copyright © 2014 John Wiley & Sons, Ltd.